TENDENCIES IN BALANCE SHEET CONSTRUCTION. - Kohler, E. L. (The Accounting Review, 1926)
Abstract In these days of business dissection and analysis, much emphasis has been put on the inferences leading from the financial position of a given enterprise in relation to its past records and to the achievements of similarly situated organizations. It is also true that comparisons of balance sheets are vital to significant financial and operating ratios and to the determination of credit indices and cyclic trends. But the lack of uniform balance sheets and uniform principles has hampered the progress of the analysts and has made more than one of them qualify his published results with such remarks as "one wishes the sources of financial data could be called reliable" or, more directly, "the reader will appreciate that the information which can be derived from published balance sheets leaves much to be desired." Most accountants have limited their excursions into the field of valuation to attempts to decide for themselves-and perhaps others-whether inventories should be valued at cost, cost of reproduction, market price, and even selling price, whether receivables may appear at present values on the balance sheet, whether bond discount must be retired on a straight-line or investment basis, whether it is proper to write off depreciation on the equal installment or sinking fund plan, whether cash discounts to customers reduce sales or increase selling or financial expenses, and so on.